PENGEMBANGAN MODUL AJAR FISIKA BERDIFERENSIASI DI SMA - Sakti, Irma; Idamayanti, Reski; Parida (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
The purpose of this study was to produce a valid and practical differentiated teaching module. This type of research is development research with the ADDIE model. The test subjects of this development product were students of class X IPA 1 SMAN 5 Maros with 36 participants. This research procedure consists of five stages, namely analysis, design, development, implementation and evaluation. The analysis stage is the initial analysis of students, curriculum analysis and analysis of student characteristics. The design stage is the needs design, material selection and teaching module design. The development stage is conducting validation. The implementation stage is implementing learning media. The evaluation stage is to make improvements to the teaching module so that it can be used. Research data obtained using validation questionnaires, and questionnaires of students' responses to development products by media experts are categorized as “valid” with a value of 3.44 and with material experts categorized as “valid” with a value of 3.36 and based on questionnaires of students' responses to teaching modules categorized as “practical” with an average response of 6.71%. So it can be concluded that the differentiated physics teaching module developed can be used in learning.